Green Synthesis of silver nanoparticles from clematis gouriana leaf extract: Physicochemical characterization and antibacterial activity determination for treatment of blood stream infections - Vinayak Yadav; Sunil T. Galatage; Arehalli S. Manjappa; Ahmad Salawi; Malleswara Rao Peram; Sameer J. Nadaf; Swapnil S. Harale (The Microbe)
Background: The global incidence of bloodstream infections (BSIs) is rising, necessitating the development of effective therapeutic strategies to achieve complete eradication. This study focuses on the synthesis of silver nanoparticles (AgNPs) functionalized with Clematis gouriana extract (CG) (CG-AgNPs) as a potential alternative to conventional treatments for combating BSIs caused by bacterial pathogens. Methods: AgNPs were synthesized by reducing silver nitrate (AgNO₃) using CG extract. The formation of CG-AgNPs was confirmed through UV-Vis spectroscopy, while their characterization included the determination of mean particle size and zeta potential. Elemental composition was analyzed using energy-dispersive X-ray (EDX) spectroscopy. The in vitro antibacterial efficacy of CG-AgNPs was assessed through multiple assays, including a time-kill assay, a film bioadhesion assay, and measurement of reactive oxygen species (ROS) generation. Results: SPR (surface plasmon resonance) has been employed to validate the development of AgNPs by observing a colour shift to dark brown. The mean particle size and zeta potential of the CG-AgNPs were found to be 38 ± 2 nm (PDI 0.104 ± 0.03) and −31.2 ± 1.4 mV, respectively. Additionally, E-XRD results show that the prepared AgNPs comply with the silver presence. The minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC) of the CG-AgNPs against Staphylococcus aureus (S. aureus) were observed to be 6.25 ± 0.8 µg/mL and 13.5 ± 2.4 µg/mL, respectively.Similarly, the MIC and MBC of CG-AgNPs against Escherichia coli (E. coli) were found to be 13.5 ± 1.5 μg/mL and 26 ± 2.8 μg/mL, respectively. CG-AgNPs also prevented biofilm formation and bacterial adhesion in a dose-dependent manner; 100 % inhibition was achieved in 48 h at MBC. In addition, CG-AgNPs remarkably escalated the ROS level within cells, indicating their mechanism of antimicarobial activity. Conclusions: The findings of this study demonstrate that CG-AgNPs synthesized via green synthesis exhibit significant antibacterial activity, highlighting their potential as an effective alternative for the treatment of BSIs. However, further in vivo studies are required to optimize a suitable dosage form and validate their therapeutic efficacy against bacterial infections in clinical settings.